The Effect of Using Real-Object Media on the Students’ Interest in Cost Estimation Learning - Nathanael Sitanggang; Putri Lynna Adelinna Luthan; Kemala Jeumpa; Hongbo Ma (Faculty of Engineering, Universitas Negeri Yogyakarta, 2019)
The rapid development of construction industry is fostering the construction service companies to hire sufficient and competent professional cost estimators who are mainly graduated from universities. This study aims to examine the students’ interest in contraction cost estimating and the effect of using real-object media and PowerPoints media in learning achievement of cost estimation. The method of this study was quasi-experimental conducted with a 2 x 2 factorial design using 40 samples. The instruments consisted of learning outcomes assesment and students’ interest testing with reliability coefficients of 0.92 and 0.81 respectively. The hypothesis was tested through variance analysis and Tukey test techniques. The research findings showed that there are interactions between the implementation of real object media and the students’ interests. For the students with high level of interest to learn, the implemetation of real object media did not give significant differences compared to the use of PowerPoints media. In the other hand, for the students with relatively low level of interest to learn, the real-object media is more effective than PowerPoints media. This finding is very useful for lecturers to improve learning achievement in cost estimation learning thus the graduates have the competence and expertise in the construction service industry.